2014
DOI: 10.1371/journal.pone.0103519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VRK2 (rs2312147) on White Matter Connectivity in Patients with Schizophrenia

Abstract: Recent genome-wide association studies of schizophrenia reported a novel risk variant, rs2312147 at vaccinia-related kinase 2 gene (VRK2), in multiple Asian and European samples. However, its effect on the brain structure in schizophrenia is little known. We analyzed the brain structure of 36 schizophrenia patients and 18 healthy subjects with regard to rs2312147 genotype groups. Brain magnetic resonance scans for gray matter (GM) and white matter (WM) analysis, and genotype analysis for VRK2 rs2312147, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…We previously also analyzed the association between VRK2 SNPs and brain phenotypes related to psychiatric disorders [34] and found that the psychiatric risk allele [C] in rs2312147 was associated with reduced total brain volume and white matter volume in healthy individuals, which was in line with clinical characteristics in the brains of psychiatric patients compared with healthy controls [73]. This finding was further supported by Sohn et al [74], as they reported significant differences in the white matter connectivity between rs2312147 CC and CT/TT genotype groups of SCZ patients for many brain regions. These data provided initial evidence for the effects of VRK2 on white matter development, and investigations dissecting the underlying biological mechanisms and etiological relevance in psychosis and mood disorders are necessary.…”
Section: Identification Of Vrk2 Variants In Psychiatric Disorders Amosupporting
confidence: 53%
“…We previously also analyzed the association between VRK2 SNPs and brain phenotypes related to psychiatric disorders [34] and found that the psychiatric risk allele [C] in rs2312147 was associated with reduced total brain volume and white matter volume in healthy individuals, which was in line with clinical characteristics in the brains of psychiatric patients compared with healthy controls [73]. This finding was further supported by Sohn et al [74], as they reported significant differences in the white matter connectivity between rs2312147 CC and CT/TT genotype groups of SCZ patients for many brain regions. These data provided initial evidence for the effects of VRK2 on white matter development, and investigations dissecting the underlying biological mechanisms and etiological relevance in psychosis and mood disorders are necessary.…”
Section: Identification Of Vrk2 Variants In Psychiatric Disorders Amosupporting
confidence: 53%
“…; Sohn et al . ) and epilepsy (EPICURE Consortium and Steffens ). Especially, there has been a steady stream of reports that VRK2 is associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Many genome-wide association studies have suggested that VRK2 is related to neurological disorders including schizophrenia (Li et al 2012;Sohn et al 2014) and epilepsy (EPICURE Consortium and Steffens 2012). Especially, there has been a steady stream of reports that VRK2 is associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the endogenous functions of VRK2 have yet to be identified. Several genome-wide association studies have described several single-nucleotide polymorphisms (SNPs) of VRK2 as risk variants for schizophrenia (rs2312147, rs3732136) and epilepsy (rs1302641) (EPICURE Consortium et al, 2012;Li et al, 2012;Sohn et al, 2014;Steinberg et al, 2011;Zhang et al, 2015). Moreover, patients with 2p15-p16.1 microdeletion syndrome (including the genomic deletion of VRK2) suffer from speech delay and learning difficulties due to impaired neurodevelopment (Chabchoub, Vermeesch, de Ravel, de Cock, & Fryns, 2008;Liang et al, 2009;Lin et al, 2008;Piccione et al, 2012;Prontera et al, 2011;Rajcan-Separovic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%